Analysis of demand for food commodities and its impact on the povert - Jumadil Saputra, Elda Elnovita, Abd. Jamal, Chenny Seftarita, (Opción, 2019)
This study is written to investigate the influence of price, income and demographic variables such as residential area and number of household members towards the demand for food commodities as sources of poverty in Aceh using the Almost Ideal Demand System (AIDS). The result of data analysis shows that prices and income have a significant effect on the demand for food commodities among poor families in Aceh. In conclusion, the sociodemographic characteristics showed that the demand for poor households in particular food commodities in an urban area is lower than in a rural area